Modified Rice Straw as a Template in Syntheses of Nano TiO2 Loaded on Wool Fibers for Wastewater Treatment - A. Atef El-Sayed; M. Salama; M. H. El-Rafie; Hossam E. Emam (Journal of Natural Fibers, 2017)
Industrialization of textile produces large amounts of colored wastewater and recycling of that wastewater is recently under the scope. The current work is implemented to use rice straw as a template for preparation of nano TiO2 to be applied in decolorization of wastewater of textile industries. Different treatments including silica removal and esterification were performed for rice straw to produce highly reactive nanotitanium dioxide. Size, morphological shape, and surface area of the so obtained TiO2 nanoparticles were observed to be influenced by rice straw treatments. Percentage of anatase phase in titanium dioxide was increased from 41.6% to 75.0% after removing of silica and modification with citric acid of rice straw. The particle size of anatase was significantly reduced from 88.6 nm to 10.5 nm while the BET surface area of nanotitanium dioxide was enlarged from 41.2 m2/g to 84.7 m2/g. The prepared TiO2 nanoparticles were loaded onto wool fibers and the photocatalytic properties of nano TiO2 powder before and after loaded to fiber were measured against methylene blue dye. The dye removal percentage raised from 92.5 to 99.2 by using of nano TiO2 powder-loaded wool fibers compared to nano TiO2 powder.